2012
DOI: 10.1515/2153-3792.1164
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Productivity of Indian Life Insurance Industry

Abstract: This paper investigates technical efficiency and productivity growth in Indian life insurance industry in the era of deregulation. The empirical study uses DEA method and Malmquist productivity index to measure and decompose technical efficiency and productivity growth, respectively. The results suggest that the growth in overall productivity is mainly attributed to improvement in efficiency. Higher pure technical efficiency and lower scale efficiency indicate the insurance firms have generally, moved away … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 0 publications
0
29
2
1
Order By: Relevance
“…The empirical results from this study suggest that technological improvement for Indian life insurance firms are very much needed to raise the efficiency and productivity (Chakraborty et al, 2011; Dutta and Sengupta, 2010). Similarly improvement in scale efficiency is highly required with higher penetration level in non-life insurance business and for both the insurance business, improvement in pure technical efficiency by enhancing physical efficiency of inputs are also badly required to maintain high efficiency levels.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The empirical results from this study suggest that technological improvement for Indian life insurance firms are very much needed to raise the efficiency and productivity (Chakraborty et al, 2011; Dutta and Sengupta, 2010). Similarly improvement in scale efficiency is highly required with higher penetration level in non-life insurance business and for both the insurance business, improvement in pure technical efficiency by enhancing physical efficiency of inputs are also badly required to maintain high efficiency levels.…”
Section: Discussionmentioning
confidence: 90%
“…There has been an extensive research examining the role of consolidation, organizational form and distributions systems in the US insurance industry such as Cummins, Tennyson and Weiss (1999), Cummins, Weiss and Zi (1999), and Berger, Cummins, and Weiss (1997). Chakraborty, Sengupta, and Dutta (2011) found that the productivity growth in life insurance industry is mainly dominated by five out of 14 most efficient firms. The technological regress is interpreted as the firms needing more inputs to produce their outputs in the terminal year (2009) compared to what they needed at the beginning of the study period (2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Saat ini, penelitian-penelitian yang telah dilakukan terkait pengukuran efisiensi dan produktivitas asuransi syariah di Indonesia masih sangat sedikit, diantaranya Benarda et al (2016), Sabiti et al (2017) dan Sunarsih & Fitriyani (2018). Umumnya penelitian tentang tingkat produktivitas juga meneliti tentang tingkat efisiensi karena dalam mengukur tingkat produktivitas menggunakan perubahan nilai efisiensi, seperti Barros et al (2005), Cummins & Xie (2013), Chakraborty et al (2013), Yaisawarng et al (2014) serta Bienera et al (2015). Penelitian tentang tingkat produktivitas asuransi syariah di Indonesia baru dilakukan terhadap perusahaan asuransi jiwa syariah (Suryoaji & Cahyono, 2019), namun belum melibatkan perusahaan asuransi umum syariah sehingga penelitian ini dimaksudkan untuk memenuhi ketiadaan tersebut.…”
Section: Pendahuluanunclassified
“…The productivity analysis of different insurance sectors has experienced rapid growth due to deregulation and liberalisation in the insurance industry (Cummins and Weiss, 2013). To the authors’ best knowledge, there are eight studies that appraise the evolution of productivity of the Indian insurance sector (Sinha, 2007a, b; Dutta, 2013; Chakraborty et al , 2013; Chakraborty, 2016, 2018; Chakraborty and Harper, 2017; Ilyas and Rajasekaran, 2019). Most of these productivity analysis studies on the Indian insurance sector evince an improvement in productivity of the insurers, which is attributable to the technological progress.…”
Section: Review Of Literaturementioning
confidence: 99%